Management of Kidney Disease with Sickle Cell Disease - Abbasi, Momen; Srivastava, Anand; Saraf, Santosh L. (Journal of the American Society of Nephrology, 2025)
Sickle cell disease is the most common inherited blood cell disorder in the United States. Vaso-occlusion and hemolysis are hallmark features of sickle cell disease that may lead to kidney damage through endothelial dysfunction and oxidative and inflammatory stress. Manifestations of sickle cell disease–related kidney disease include hyperfiltration that occurs early in the disease course followed by albuminuria and a progressive decline in eGFR. Patients with sickle cell disease have a faster rate of eGFR decline and the development of CKD is associated with higher morbidity and early mortality. The assessment of kidney function is challenged by the transition from the hyperfiltration phase to reduced eGFR and by tubular creatinine secretion, which may lead to overestimation of the true GFR. Cystatin C–based and race-free estimating GFR equations reduce the overestimation but require further validation. Complications of kidney dysfunction include hyperkalemia and metabolic acidosis that occur at higher eGFR thresholds compared with the general population. Coinheritance of genetic variants, such as APOL1 G1 and G2 kidney risk variants, may help identify patients with sickle cell disease at higher risk for CKD and guide treatment and screening strategies. Therapeutic approaches targeting the sickle cell disease pathophysiology, such as hydroxyurea, chronic red blood cell transfusions, and hematopoietic stem cell transplantation, have demonstrated some kidney protective effects, but larger studies with longer follow-up are needed. Novel agents, including endothelin receptor antagonists, pyruvate kinase activators, and APOL1 inhibitors, are currently under investigation. Kidney-protective therapies such as renin-angiotensin-aldosterone system inhibitors and sodium-glucose cotransporter 2 inhibitors offer promise but require prospective validation in sickle cell disease cohorts. Kidney transplantation is associated with better survival and should not be withheld based solely on sickle cell disease diagnosis. Early identification, individualized management, and ongoing research are essential to improve kidney outcomes and reduce mortality in this high-risk population.